Comparing Biomechanical Properties, Repair Times, and Value of Common Core Flexor Tendon Repairs. (May 2018) - Chauhan, Aakash; Schimoler, Patrick; Miller, Mark C.; Kharlamov, Alexander; Merrell, Gregory A.; Palmer, Bradley A.
Background: The aim of the study was to compare biomechanical strength, repair times, and repair values for zone II core flexor tendon repairs.Methods: A total of 75 fresh-frozen human cadaveric flexor tendons were harvested from the index through small finger and randomized into one of 5 repair groups: 4-stranded cross-stitch cruciate (4-0 polyester and 4-0 braided suture), 4-stranded double Pennington (2-0 knotless barbed suture), 4-stranded Pennington (4-0 double-stranded braided suture), and 6-stranded modified Lim-Tsai (4-0 looped braided suture). Repairs were measured in situ and their repair times were measured. Tendons were linearly loaded to failure and multiple biomechanical values were measured. The repair value was calculated based on operating room costs, repair times, and suture costs. Analysis of variance (ANOVA) and Tukey post hoc statistical analysis were used to compare repair data.Results: The braided cruciate was the strongest repair ( P > .05) but the slowest ( P > .05), and the 4-stranded Pennington using double-stranded suture was the fastest ( P > .05) to perform. The total repair value was the highest for braided cruciate ( P > .05) compared with all other repairs. Barbed suture did not outperform any repairs in any categories.Conclusions: The braided cruciate was the strongest of the tested flexor tendon repairs. The 2-mm gapping and maximum load to failure for this repair approached similar historical strength of other 6- and 8-stranded repairs. In this study, suture cost was negligible in the overall repair cost and should be not a determining factor in choosing a repair.